2017
DOI: 10.1002/fsn3.550
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the glycemic indices of three commonly eaten mixed meals in Okada, Edo State

Abstract: People do not generally eat single or individual meals; rather they eat mixed meals, consisting of two or more individual meals. These mixed meals usually have glycemic indices which differ from that of the individual food type. This study was aimed at evaluating the glycemic indices of three commonly consumed mixed meals eaten in Okada; rice and beans (test food 1), rice and plantain (test food 2), beans and plantain (test food 3). Two hundred and forty healthy subjects aged between 18 and 30 participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
8
0
4
Order By: Relevance
“…12 Ripe bean seeds have positive benefits regarding lowering the blood glucose response. 13 A similar study also found that ripe plantain has similar beneficial effects. 13 Another study looked at the combination of rice with lentils and showed a positive effect on the postprandial GR in healthy individuals.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…12 Ripe bean seeds have positive benefits regarding lowering the blood glucose response. 13 A similar study also found that ripe plantain has similar beneficial effects. 13 Another study looked at the combination of rice with lentils and showed a positive effect on the postprandial GR in healthy individuals.…”
Section: Resultsmentioning
confidence: 68%
“…13 A similar study also found that ripe plantain has similar beneficial effects. 13 Another study looked at the combination of rice with lentils and showed a positive effect on the postprandial GR in healthy individuals. 14 Thus, based on these current evidences, co-ingestion of legumes can help to attenuate postprandial GR.…”
Section: Resultsmentioning
confidence: 68%
“…The remaining studies were used for the selection of low-GI carbohydrate-based foods [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. All studies reported changes in glycemic index, four studies [ 7 , 17 , 18 , 19 ] reported changes in amylose content to GI, ten studies [ 9 , 10 , 11 , 12 , 13 , 20 , 21 , 22 , 23 , 24 ] reported changes in resistant starch (RS) content to GI, fifteen studies reported a change in dietary fibre content to GI, fifteen studies reported a change in fat content to GI, fifteen studies reported a change in protein content to GI, twelve studies reported a change in phenol content to GI, ten studies reported a change in flavonoid content to GI, five studies reported a change in cereal type to GI, six studies reported a change in tuber type to GI, two studies reported a change in fruit type to GI, and four studies reported a change in legume type to GI. Detailed characteristics of eligible studies are presented in Table 2 and Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from randomized controlled trials (RCTs) was reported to be inconsistent [ 4 , 6 , 7 ], while no report was found using systematic review [ 8 ] or meta-analysis [ 9 ]. Furthermore, five recent trials [ 10 , 11 , 12 , 13 , 14 ] with adequate power have been published and involved new evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Indeks glikemik dan beban glikemik. Uji indeks glikemik dilakukan menggunakan desain rancangan one shot case study yaitu memberikan perlakuan secara sengaja kepada subjek berupa makanan acuan (air gula yang mengandung 25 gram available carbohydrates) dan formula enteral tepung tempe dan bengkuang kemudian mengukur glukosa darah setelah perlakuan [29,30]. Sehari sebelum perlakuan, subjek diharuskan berpuasa (kecuali air putih) selama 10 jam mulai pukul 22.00 sampai 08.00 pagi berikutnya.…”
Section: Pengumpulan Dan Pengukuran Dataunclassified